Measure twice, cut once: pitfalls in the diagnosis of supraventricular tachycardia - Chaldoupi, S.M. (Bohn Stafleu van Loghum, 2010)
In atrioventricular nodal and atrioventricular reentrant tachycardia, the relative timing of atrial and ventricular activation may sometimes be very similar, even during electrophysiological studies, and this may lead to an erroneous diagnosis and inappropriate treatment. As examples, we describe two cases that were recently referred to our hospital for a second opinion and treatment of paroxysmal supraventricular tachycardia. In both, the original diagnosis of the referring centres was commontype atrioventricular nodal reentrant tachycardia. Catheter ablation in those centres was unsuccessful. During our electrophysiological studies, however, an atrioventricular reentrant tachycardia was demonstrated, using a concealed accessory pathway for retrograde conduction in both patients. The accessory atrioventricular connection was successfully ablated and on follow-up both patients remained free of symptoms without medication. These findings illustrate the importance of complete electrophysiological analysis even for apparently simple supraventricular arrhythmias. (Neth Heart J 2010;18:78–84.)